Epidemiological Insights into Erectile Dysfunction in the United States: A Google Trends Analysis - Zaid Ahmed; Muhammed A. Moukhtar Hammad; Jake Miller; Elia Abou Chawareb; Lawrence C. Jenkins; Faysal A. Yafi (Société Internationale d’Urologie Journal)
Background/Objectives: Erectile dysfunction (ED) significantly impacts the well-being and quality of life of millions of men. Understanding geographic patterns and associated factors influencing ED search trends can offer valuable insights for healthcare improvement and advocacy. This study investigated the correlation between Google search trends for ED and various factors across the US. Methods: Google search trends for “erectile dysfunction” were collected over a 6-year period between March 2018 and August 2024. The Google search trends provided data for individual states on a scale from 1 to 100. Search volumes were analyzed alongside the urologist-to-population ratio, percentage of the population aged 65 and older, median household income, and percentage of state residents with a bachelor’s degree or higher. Pearson correlation coefficients were used to examine the relationships between ED search volumes and these factors. Results: Higher ED search volumes were associated with a higher percentage of older adults (r = 0.4332, p = 0.001676). A negative correlation was found between ED search volume and higher education (r = −0.482, p = 0.000394). No significant correlation was found between median household income and ED search volume (r = −0.201, p = 0.164) or a greater urologist density (r = 0.0612, p = 0.6729). Conclusions: This study highlights how healthcare access and demographics influence ED search trends. States with older, less educated populations showed higher interest, while wealthier areas with more urologists had no significant correlation. These findings can guide targeted interventions to improve sexual care in underserved regions.